International auditing standards between theory, practice, and its application in the Kurdistan Region -Iraq - امىدرس امىساغد گؤران حسي كادر; امىدرس امىساغد دەرةاز أًِر إسىاغٔل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study dealt with the international audit standards and the extent of their suitability for application in the republic of Iraq. It was a field study of Kurdistan Region. The aim of the study was to know the effect of the environmental facts on the application of the international audit standards in the Region. The study reached a number of findings. Among the important ones is that the application of the international audit standards in Kurdistan Region affects the accounting and auditing environment according to the views of the sample of the study. There is unawareness of scientific and practical qualifying standards of the auditors in Kurdistan Region. The research recommends the approval of the international standards of audit and control over the work quality of auditing.